The Relationship Between Elevated D-Dimer Levels And The Incidence Of Ischemic Stroke In Covid-19 Patients At Drs H. Amri Tambunan Regency, Deli Serdang Regency - Novani, Dinda Dwi; Surya, Anita; Arifin, Hasanul; Irma, Fani Ade (Universitas Muhammadiyah Sumatera Utara, 2027)
Abstract: Acute ischemic stroke spreads from infected individuals, whether they are already showing symptoms or not. The initial symptom that often appears in infected individuals is fever, with a body temperature between 38.1 and 39°C. The mechanism of stroke in COVID-19 patients is caused by an increase in D-Dimer and fibrinogen, which are part of the coagulation pathway. Coagulation is related to the systemic inflammatory response caused by infection. The purpose of this study was to understand and further examine the relationship between increased D-Dimer levels in ischemic stroke patients infected with COVID-19 at Drs. H. Amri Tambunan Regional Hospital, Deli Serdang Regency. This research method is a retrospective descriptive study using a cross-sectional research design. This study used secondary data derived from medical records of COVID-19 patients with ischemic stroke events at Drs. H. Amri Tambunan Regional Hospital, Deli Serdang Regency. H. Amri Tambunan, Deli Serdang Regency, 2021. The results of the Chi-square test were 0.239 (P-value 0.05), which means there is no significant relationship between increased D-Dimer and the incidence of ischemic stroke and hemorrhagic stroke in COVID-19 patients. The conclusion obtained was that there was no significant relationship between increased D-Dimer and the risk of ischemic stroke in COVID-19 patients.